HAMZAH FANSURI’S PHILOSOPHICAL TASAWWUF: A CONCEPT OF WUJUDIYYAH - Saputra, Gebby Endra (UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
This research focuses on the kalam thought of Hamzah Fansuri, a well-known Sufi in Nusantara. Many view Hamzah Fansuri's teachings as promoting pantheism, the belief that the universe is a manifestation of God. This research uses the library method and is descriptive-analytical, describing Hamzah Fansuri's thought and analyzing his kalam thought. The results of the research show that Hamzah Fansuri's kalam thought is oriented towards the concept of wujudiah, the belief that the highest truth of human faith is ma'rifat, a state where one is united with God. In the process, a salik (Sufi traveler) needs the guidance of a guru or mursyid who will help them achieve the true level of ma'rifat and reach the level of self-annihilation (Fana' fi Allah). The wujudiyah concept of Hamzah Fansuri has a wide influence and gives a falsafi color to the Sufi tradition that developed in Nusantara. Hamzah Fansuri is an early Islamic figure in Nusantara who played an important role in the development of Islam in Indonesia.